PRODUCTION OF THE Kappaphycus alvarezii EXTRACT AS A LEAF BIOFERTILIZER: TECHNICAL AND ECONOMIC ANALYSIS FOR THE NORTH COAST OF SÃO PAULO-BRAZIL - Valeria Cress GELLI; Marco Túlio Ospina PATINO; Jansle Vieira ROCHA; Edison BARBIERI; Kleber Campos MIRANDA-FILHO; Marcelo Barbosa HENRIQUES (Boletim do Instituto de Pesca)
The extract of the Kappaphycus alvarezii seaweed is used as a leaf biofertilizer and several studies had proven its efficiency in several crops. This study aimed to analyze the economic viability of fresh seaweed production and the chemically characterized seaweed extract cultivated as a technical-economic alternative for coastal communities. Yields of the solid and liquid fractions were quantified, the extract was characterized in its chemical composition of macronutrients and micronutrients and it was classified according to the criteria of the Brazilian legislation of agricultural fertilizers. For the study of economic feasibility, different sales price scenarios were considered and compared with the commercialization of fresh seaweed. The average yield obtained from the processing of the Brazilian adapted strains of the K. alvarezii for the liquid fraction or fresh seaweed extract was 0.71 ± 0.0080 L kg-1 and the moisture solid production was 295 ± 0.0126 g kg-1. The production of fresh seaweed was unfeasible and for the handmade extract was economically viable for the scenario with the sale price of US$ 2.77 with a net present value of US$ 35,300.13 and an internal rate of return (IRR) of 38.99% over ten year.